MANAGEMENT PROPOSAL FOR THE MASSIVE COURSES IN THE UPC'S SCIENCE AREA BASED OF THE CIRCLES AND HELICOIDS OF THE KNOWLEDGE THEORY - Viale Tudela, Héctor Ernesto (2008)
In the presence of exponential growth in the country’s universities’ population, it is necessary to reflect upon the management of massive courses1 in the first semesters. This doesn’t only imply to adequately orient, educate and insert an elevated number of students to university life. There’s also a need to coordinate with an important number of teachers who must develop classroom material and academic documents necessary for the good development of the teaching-learning system, following the UPC’s pedagogic model. A management that gives importance to the completion of established times by the shift coordinator, in detriment of the production and transmission of knowledge, is destined to fail. This article proposes that the management of massive courses, in a context like the one mentioned in the first lines, must be based on the production and management of knowledge. It invites all of the teachers to actively and creatively participate in course design and in the elaboration of materials and documents. According to the author, this form of conduct can be achieved through the circles and helicoids of knowledge.